PENGARUH PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP BELANJA LANGSUNG PEMERINTAH DAERAH (Studi pada Kabupaten/Kota Se-Sulawesi Tengah) - Melas, Agus (Katalogis, 2017)
The study intends to determine and analyze the growth of local tax, local retributions, and direct expenditure as well as simultaneous and partial impacts od local tax and local retributions on direct expenditure. Sample of this study consists of 11 districts/cities that selected through nonprobability sampling method. Type of study is descriptive with quantitative approach and method of analysis is multiple linear regressions . The results shows that in average, the growth of income from local tax and retributions has been decreasing in three years, as well as direct expenditure. Simultaneous test shows that local tax and retribution have significant impact on direct expenditure. Similarly, partial test also evidences that local tax and retributions have impact on direct expenditure. Determinant coefficient shows that R-square of 0,585 indicates that 58,50% of direct expenditure impacted by local tax and retribution, while 41,50% impacted by variables that are not studied.